2020
DOI: 10.12998/wjcc.v8.i19.4450
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-year survival after iterative surgery for metastatic renal cell carcinoma: A case report and review of literature

Abstract: BACKGROUND The therapeutic approach of metastatic renal cell carcinoma (RCC) represents a real challenge for clinicians, because of the variable clinical course; the recent availability of numerous targeted therapies that have significantly improved overall oncological results, but still with a low percentage of complete responses; and the increasing role of metastasectomy (MSX) as an effective strategy to achieve a durable cure, or at least defer initiation of systemic therapies, in selected pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
(127 reference statements)
0
7
1
Order By: Relevance
“…Here we report a rare case of RCC that presented with lung metastasis 16 years after nephrectomy. Based on our literature review, we found only ten reported cases with intervals longer than in our case between nephrectomy for RCC and lung metastasis: 17 years [5], 19 years [6], six cases with 20-28 years intervals [7], 31 years [8], and 37 years [9].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Here we report a rare case of RCC that presented with lung metastasis 16 years after nephrectomy. Based on our literature review, we found only ten reported cases with intervals longer than in our case between nephrectomy for RCC and lung metastasis: 17 years [5], 19 years [6], six cases with 20-28 years intervals [7], 31 years [8], and 37 years [9].…”
Section: Introductionmentioning
confidence: 76%
“…RCC recurs after more than 10 years of nephrectomy in 10% of the cases [11]. The most common sites of metastasis include lungs, bones, lymph nodes, adrenal glands, liver, brain contralateral kidney, and pancreas [5]. Metastatic clear cell RCC has a poor prognosis with a median overall survival of 12 months only which has improved in the last decade [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 The most common sites of metastasis include lungs, bones, lymph nodes, adrenal glands, liver, brain, contralateral kidney, and pancreas. 5 Metastatic clear cell RCC has a poor prognosis with a median overall survival of 12 months only which has improved in the last decade. 12 Pulmonary metastasis from RCC after a long interval is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Is systematic lymph node dissection always required when performing lung metastasectomy, or should it be offered in selected cases only? Which patients can benefit of iterative surgical excision of secondary lung localizations and what is the expected survival benefit (13)(14)(15)(16)?…”
mentioning
confidence: 99%